Comparative field study: impact of laboratory assay variability on the assessment of recombinant factor IX Fc fusion protein (rFIXFc) activity - Sommer, Jurg M.; Buyue, Yang; Bardan, Sara; Peters, Robert T.; Jiang, Haiyan; Kamphaus, George D.; Gray, Elaine; Pierce, Glenn F. (Thrombosis and Haemostasis, 2014)
Due to variability in the one-stage clotting assay, the performance of new factor IX (FIX) products should be assessed in this assay. The objective of this field study was to evaluate the accuracy of measuring recombinant FIX Fc fusion protein (rFIXFc) activity in clinical haemostasis laboratories using the one-stage clotting assay. Human haemophilic donor plasma was spiked with rFIXFc or BeneFIX® at 0.80, 0.20, or 0.05 IU/ml based on label potency. Laboratories tested blinded samples using their routine one-stage assay and in-house FIX plasma standard. The mean spike recoveries for BeneFIX (n=30 laboratories) were 121 %, 144 %, and 168 % of expected at nominal 0.80, 0.20, and 0.05 IU/ml concentrations, respectively. Corresponding rFIXFc spike recoveries were 88 %, 107 %, and 132 % of expected, respectively. All BeneFIX concentrations were consistently overestimated by most laboratories. rFIXFc activity was reagent-dependent; ellagic acid and silica gave higher values than kaolin, which underestimated rFIXFc. BeneFIX demonstrated significantly reduced chromogenic assay activity relative to one-stage assay results and nominal activity, while rFIXFc activity was close to nominal activity at three concentrations with better dilution linearity than the typical one-stage assay. In conclusion, laboratory- and reagent-specific assay variabilities were revealed, with progressively higher variability at lower FIX concentrations. Non-parallelism against the FIX plasma standard was observed in all one-stage assays with rFIXFc and BeneFIX, leading to significant overestimation of FIX activity at lower levels and generally high inter-laboratory variability. Compared to the accuracy currently achieved in clinical laboratories when measuring other rFIX products, most laboratories measured rFIXFc activity with acceptable accuracy and reliability using routine one-stage assay methods and commercially available plasma standards.
Keywords: Activated partial thromboplastin time (aPTT); coagulation factor IX; haemophilia B; coagulation tests; blood; standardisation